RACE, RELIGION, AND THE MORAL OF WHITENESS: A POSTCOLONIAL READING OF NADINE GORDIMER’S COUNTRY LOVERS - Dian Nurrachman; Dody S. Truna; Ilim Abdul Halim; Mohammad Ziaul Haq (Saksama: Jurnal Sastra, 2025)
This article examines Nadine Gordimer’s Country Lovers through an integrated framework drawn from postcolonial criticism, critical race theory, and the genealogy of religion. It argues that Gordimer’s short story offers a concentrated narrative archive of how race and religion function as co-constitutive systems of colonial power. Using a mimetic method of literary criticism, the study treats the narrative as a representational site where social, legal, and moral structures of apartheid South Africa are reproduced and contested. The analysis is grounded in the contemporary understanding of race as a sociohistorical construct whose apparent naturalness conceals political and institutional production. The study also draws on Talal Asad’s formulation of religion as a historically contingent category shaped by European intellectual and colonial histories, as well as Malory Nye’s and Theodore Vial’s arguments that race and religion are inseparable “conjoined twins” of modernity. Within this theoretical constellation, Country Lovers emerges as a text that discloses how Christian-inflected moral orders and secular legal practices jointly uphold racial hierarchies. Close readings of key narrative scenes—Paulus and Thebedi’s secret encounters, the description of the mixed-race infant, the court proceedings, and Thebedi’s coerced silence—demonstrate the ways in which whiteness operates as moral purity while blackness is aligned with sin, transgression, and disposability. By analyzing these narrative elements as mimetic representations of structural power, the article argues that Gordimer’s work illuminates the afterlives of colonial religio-racial discourse in modernity. Ultimately, the study contends that Country Lovers not only critiques apartheid but also exposes the deeper moral and epistemic architectures through which colonialism continues to shape postcolonial consciousness. The article contributes to broader scholarly conversations about decolonization by foregrounding literature as a site where racialized religious imaginaries are produced, contested, and potentially transformed.